Basics of Nuclear Radiation - Ali Abid Abojassim; Rusul Hadi Hashim; Najlaa Saleh Mahdi (Basics of Nuclear Radiation, 2021)
This book has fourteen chapters, the first chapter deal with the history of nuclear radiation, the second and third chapters deal with sources and types of nuclear radiation. Chapter four explained the X-ray in more detail. Radiation quantity, radiation interaction with mater, and radioisotopes were written in chapters five, six, and seven, respectively. Chapters eight and nine study the use and hazard of nuclear radiation on humans. Chapter ten was studying nuclear detectors according to types and it works. The subject of the protection of nuclear radiation was explained in chapter eleven. Chapters twelve and thirteen have the important pollution source in the background depleted Uranium and radon gas. Finally, nuclear and radiation accidents were written and put many pictures for the importance of radiation accidents that happen in the world.